Different sensitivities of senescent breast cancer cells to immune cell‐mediated cytotoxicity. Issue 9 (23rd July 2019) - Inao, Touko; Kotani, Hitoshi; Iida, Yuichi; Kartika, Irna Diyana; Okimoto, Tamio; Tanino, Ryosuke; Shiba, Eiichi; Harada, Mamoru
Abstract: Senescence is a state of growth arrest induced not only in normal cells but also in cancer cells by aging or stress, which triggers DNA damage. Despite growth suppression, senescent cancer cells promote tumor formation and recurrence by producing cytokines and growth factors; this state is designated as the senescence‐associated secretory phenotype. In this study, we examined the susceptibility of senescent human breast cancer cells to immune cell‐mediated cytotoxicity. Doxorubicin (DXR) treatment induced senescence in 2 human breast cancer cell lines, MDA‐MB‐231 and BT‐549, with the induction of γH2AX expression and increased expression of p21 or p16. Treatment with DXR also induced the expression of senescence‐associated β‐galactosidase and promoted the production of pro‐inflammatory cytokines. Importantly, DXR‐treated senescent MDA‐MB‐231 cells showed increased sensitivity to 2 types of immune cell‐mediated cytotoxicity: cytotoxicity of activated CD4 + T cells and Ab‐dependent cellular cytotoxicity by natural killer cells. This increased sensitivity to cytotoxicity was partially dependent on tumor necrosis factor‐related apoptosis‐inducing ligand and perforin, respectively. This increased sensitivity was not observed following treatment with the senescence‐inducing cyclin‐dependent kinase‐4/6 inhibitor, abemaciclib. In addition, treatment with DXR, but not abemaciclib, decreased the expression of antiapoptotic proteins in cancer cells. These results indicated that DXR and abemaciclib induced senescence in breast cancer cells, but that they differed in their sensitivity to immune cell‐mediated cytotoxicity. These findings could provide an indication for combining anticancer immunotherapy with chemotherapeutic drugs or molecular targeting drugs. Abstract : Doxorubicin‐induced senescence‐associated β‐Gal in human breast cancer cells.